SYNTHESIS, SPECTRAL AND MOLECULAR MODELING STUDIES OF COUMARIN DERIVATIVES - Bhaskar, P. Vijay; Ramachandraiah, A. (International Journal of Current Pharmaceutical Research, 2017)
Objective: To synthesize the 3-{2-[N'-(1-Pyridin-2-yl-ethylidene)-hydrazino]-thiazol-4-yl} coumarins and study their spectral and molecular properties by using the spectroscopy and molecular modeling techniques. Methods: Spectroscopy and Molecular modeling techniques Results: The spectral behavior of 3-{2-[N'-(1-Pyridin-2-yl-ethylidene)-hydrazino]-thiazol-4-yl} coumarins (1.1-1.3) in aqueous buffers of varied pH is presented. Spectrophotometry was utilized to study its proton and electron transfer characteristics with the support of molecular modeling studies. An excellent analytical method of assaying of (1.1-1.3) has been developed in Spectrophotometry at pH = 6. Molecular modeling on various acid-base conjugates of (1.1-1.3) and their several conformers has been carried out to arrive at the thermodynamic and conformational issues to correlate the spectral and electrochemical observations. Conclusion: Electron transfer (ET) has been increasingly implicated as a biochemical pathway for the pharmacologic action of a variety of biological active compounds. These studies helps to understand the active form of the biological active compounds may have a catalytic function as an intermediary in passing electrons from a donor, such as DNA, protein, or an ET chain, to an acceptor, thereby exercising an influence on normal or aberrant ET chains, ion movements, membrane potentials, and oxidative stress. The actual agent may be the biological active compounds itself or a derived metabolite, such as a metal complex, oxidative product, or protonated form.